Integrated geometrical and dimensional tolerances stack-up analysis for the design of mechanical assemblies: an application on marine engineering. Issue 5 (3rd September 2018) - Renzi, Cristina; Ceruti, Alessandro; Leali, Francesco
ABSTRACT: This paper presents a knowledge based engineering environment methodology to support the designer in the correct setting of geometrical and dimensional tolerances in assemblies of mechanical components. The procedure is based on the definition of the functional requirements needed to allow the proper working of the assembly; in the further, a software tool is used to do a statistical analysis of the assembly relations, providing an estimation of the components waste due to poor compliance to the tolerances. A case study given by the design of a marine power transmission is presented: the methodology leads to the change of some tolerances to improve the design by reducing the number of waste components. The strength of the methodology is represented by the fact it can help unskilled designers in the correct setting of tolerances in drawings. GRAPHICAL ABSTRACT: